How Parents of Children with Cancer Seek Information Through Online Communities: A Netnography Study - Canan Sümeyra Gün; Selmin Şenol (Galenos Yayinevi, 2019)
Aim:This study aims to examine how parents of children with cancer seek information through online communities, using netnography methods from qualitative study types.Materials and Methods:The study was carried out through two online communities where parents of children with cancer in Turkey communicate with each other. The data were obtained from the parents' posts to online community platforms covering the period between September 2nd and November 2nd, 2017. The data were collected using the netnography method and analyzed within the principles of this method.Results:A total of 580 written posts (information sharing) were sent within the interval in which the study was conducted, and 208 of them, which were posted by 131 parents, were analyzed and coded. Accordingly, three themes were defined in terms of codes as follows: "disease," "treatment and side effects", and "non-treatment" posts. The themes of "disease" and "treatment and side effects" included questions in which the parents were seeking information, whereas the theme of "non-treatment" mostly included posts in which the parents were seeking emotional support from other parents in the communities.Conclusion:The way in which parents of children with cancer seek information through online communities is mostly related to their questions and posts parallel to the cancer process. In this process, the parents were found to seek emotional support.